Open Data Kit (ODK) in crop farming: an introduction of mobile data collection methods in seed yam tracking in Ibadan, Nigeria - Ouma, T.A. (Jomo Kenyatta University of Agriculture and Technology, 2020)
The purpose of this paper is to illustrate the importance of applying open-source technologies for mobile-based data collection for real-time tracking of seed yam (Dioscorea rotundata and Dioscorea alata) production. Seed yam data in Nigeria have been predominantly collected using field notebooks in the past, which were subsequently entered into a Microsoft Excel spreadsheet or Access database for analysis and reposition. Relevant areas of weakness within the current data systems include time delay in providing feedback and non-availability of data upon demand. As a result, this has hampered direct tracking of seeds at various stages of crop production and management. The main research objective is to develop a seed yam-tracking application using ODK that addresses these data collection challenges. The specific objectives are to evaluate the challenges relative to the existing data collection systems and reporting methods in seed yam production; to evaluate the effectiveness of the prototype developed for collection, entry and capture of seed yam production data; and to improve aggregation of field data and real time visualization of data using mobile technologies. The study provided data collectors with a pre-installed yam seed tracking app for use on an Android device for data collection and management. The system architecture is based on the Open Data Kit (ODK) framework and a custom design based on requirements and lessons learned from literature. The ODK (Aggregate) made data easily accessible in minimum time possible from the point of data collection. The yam seed tracking application was developed as a result and field tested. The results indicated that this method improved efficiency, speed, and convenience in data collection and visualization. Farmers were able to make timely management decisions, ultimately boosting crop productivity.